A fotografia como recurso didático na educação ambiental - Freisleben, Alcimar Paulo (2013)
The photographic image is above all an attempt to unify and overcome the fragmentation and compartmentalization of knowledge and focuses the environmental education. This work presents a discussion about some didactics possibilities in the use of photography as a methodological resource of teaching, aimed at raising awareness of environmental issues and training critical student. We work with twenty-six students eighteen authors students and eight students not authors of the photographs during the Geography classes of high school, at the public college Dr. Eduardo Virmond Suplicy, in Francisco Beltrão city, Brazil. The research was structured through the capture and subsequent analysis of the city landscape photographs. For we understand better how the use of imaging and photography are being used in classrooms, eight active teachers and one notactive teacher participated of the research. Among the teachers, eight are licensed in Geography and one of them is licensed in Arts. They teach courses in several areas, at elementary and high school, and universities, in public and private institutions of the Paraná state, Brazil. Thirty-five individuals took part, being twenty-six students and nine teachers. We seek to evaluate the potential didactic from the photography in the teaching and Environmental Education. Therefore we constructed a digital image collection that is available in DVD annexed. There are many didactics possibilities from the photography, both printed as projected in the media or on TV Pen-drive, as well as the photographs from blogs and photoblogs. They are ways that can be inserted daily at the school. The selection of photographs appropriate to the activity is very important, as well the teacher must be able to promote debates with the students for a critical analysis of the photographs, unveiling the photography meanings, correlating the images with the lesson theme and with the pedagogical objectives intended.